2016
DOI: 10.1177/0394632016635656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for atopic disease in a population of preschool children in Rome: Challenges to early intervention

Abstract: This study represents a first comprehensive epidemiological evaluation of prevalence of respiratory and allergic diseases in children aged 3-5 years in the city of Rome and an updating of the evolution of allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
(48 reference statements)
3
12
1
3
Order By: Relevance
“…We found a prevalence of wheeze in the 12 months before assessment of 31.4%, which is much higher than the 15% recently reported in the general population of Italian preschool children. 30 This finding confirms previous reports of a two-to three-fold higher prevalence of respiratory symptoms in very preterm children compared with term-born controls independently of BPD. 7,9 The observation that in our children at preschool age symptoms correlate with high resistance and low compliance is of concern.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found a prevalence of wheeze in the 12 months before assessment of 31.4%, which is much higher than the 15% recently reported in the general population of Italian preschool children. 30 This finding confirms previous reports of a two-to three-fold higher prevalence of respiratory symptoms in very preterm children compared with term-born controls independently of BPD. 7,9 The observation that in our children at preschool age symptoms correlate with high resistance and low compliance is of concern.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, in area‐based prospective cohorts where a number of maternal and perinatal variables or GA were studied in relation to lung function indices at school age no relationship was found. We found a prevalence of wheeze in the 12 months before assessment of 31.4%, which is much higher than the 15% recently reported in the general population of Italian preschool children . This finding confirms previous reports of a two‐ to three‐fold higher prevalence of respiratory symptoms in very preterm children compared with term‐born controls independently of BPD .…”
Section: Discussionsupporting
confidence: 85%
“…Распространенность и факторы риска АР среди детей дошкольного возраста в международных эпидемиологических исследованиях не изучались. В отдельных национальных зарубежных исследованиях показано, что распространенность АР среди детей дошкольного возраста в Китае варьирует в зависимости от региона от 7,3 до 22,5% [5,6], в Южной Корее достигает 20,8% [7], в Италии -5,5% [8], в США -13,7% [9]. По данным исследований, в 2017 г. распространенность АР среди дошкольников Турции составляла 13,4% [10], Австралии -8,3% [11], Южной Кореи -17,3% [12].…”
Section: обоснованиеunclassified
“…Оба опросника выдавали родителям/законным представителям ребенка для самостоятельного заполнения на этапе скрининга. В исследованиях, где распространенность АР изучалась с помощью опросников, показатели были либо выше [22][23][24], либо ниже [5,8,11] полученных нами. Таким образом, различия могут быть связаны прежде всего с разными методами диагностики АР -на основании опросников или критериев ARIA, а также с возрастной неоднородностью детей и климатогеографическими особенностями стран.…”
Section: клиническая оценка арunclassified
“…Conducted on over 20,000 children 6–7 years old and on 16,000 adolescents in two phases (1994 and 2002), the SIDRIA study showed a clear increase in the prevalence of asthma in both groups [2, 3]. A much more recent study conducted in Rome confirmed these prevalence data in a population of preschool children (3–5 years old): 15% of children experienced at least one episode of wheezing, and 11% had a doctor’s diagnosis of asthma [4]. The frequency of allergic sensitization in this age group was already as high as 12%, while, currently, the prevalence of allergic sensitization abundantly exceeds 30% of the 10–14-year-old population, with peaks exceeding 40%.…”
Section: Introductionmentioning
confidence: 99%